1992
DOI: 10.1152/ajpheart.1992.263.2.h372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on vasomotor reactivity of porcine coronary arteries

Abstract: The purpose of this study was to determine whether exercise training induces changes in the contractile behavior of proximal coronary arteries. Female Yucatan miniature swine were either exercise trained (ET) on a motor-driven treadmill or allowed to remain sedentary (SED) for 16-22 wk. Responses to vasoactive compounds were evaluated in vitro using coronary arterial rings (approximately 2 mm diam) isolated from ET and SED pigs. Each ring was stretched to the apex of the length-active tension relationship. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 0 publications
8
65
1
2
Order By: Relevance
“…Thoracic aorta from rats submitted to swimming during 6 weeks showed a decrease in response to PE, but not to potassium chloride, 25 as also reported in porcine coronary arteries. 26 The aortic subsensitivity to PE observed after anaerobic training in the present study suggests that even in response to the metabolic demands of different physical exercises (aerobic versus anaerobic), vascular adaptations are established to promote a decrease in arterial blood pressure. Moreover, this response can be related to endothelial adaptations to the higher blood flow induced by aerobic and anaerobic exercise training.…”
Section: Discussionmentioning
confidence: 55%
“…Thoracic aorta from rats submitted to swimming during 6 weeks showed a decrease in response to PE, but not to potassium chloride, 25 as also reported in porcine coronary arteries. 26 The aortic subsensitivity to PE observed after anaerobic training in the present study suggests that even in response to the metabolic demands of different physical exercises (aerobic versus anaerobic), vascular adaptations are established to promote a decrease in arterial blood pressure. Moreover, this response can be related to endothelial adaptations to the higher blood flow induced by aerobic and anaerobic exercise training.…”
Section: Discussionmentioning
confidence: 55%
“…However, in spite of the disagreement among findings with regard to the acute effect of exercise on vasoconstriction response to norepinephrine, it seems to be a consensus that one of the chronic beneficial effects of aerobic exercise is the attenuation of adrenergic vasoconstriction (Oltman et al, 1992;Chen et al, 1994;Spier et al, 1999;McAllister et al, 2005), which presents important clinical relevance, since this response is increased in the majority of circulation system pathologies and cardiovascular risk factors (Stepp and Frisbee, 2002;Ajay and Mustafa, 2006; Koida et al, 2006;Lesniewske et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that there is an attenuation of adrenergic receptor-dependent vasoconstriction after a single bout of exercise (Howard et al, 1992;Izawa et al, 1996;Ruble et al, 2002), while other studies have not found this attenuation response (Delorey et al, 2007), or have observed it only after some weeks of exercise training (Oltman et al, 1992;Spier et al, 1999). With regard to the acute effect of exercise on adrenergic receptor-independent vasoconstrictor response, only a small number of studies were conducted, where only a tendency for an attenuation of vasoconstrictor response to potassium chloride (KCl) has been observed (Howard et al, 1992;Spier et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that Ca 2ϩ entering the cell through L-type voltage-gated Ca 2ϩ channels is sequestered by SERCA on the superficial SR and slowly released from the SR toward sarcolemmal Ca 2ϩ -ATPase and the Na ϩ /Ca 2ϩ -exchanger for extrusion (8,17,41,42). This adaptation to exercise has been described as a mechanism to attenuate vasoconstriction to potent Ca 2ϩ -mobilizing agonists, i.e., endothelin-1 (8) and norepinephrine (33), by depleting the SR Ca 2ϩ store. Thus SERCA localization Ͻ200 nm from the sarcolemma is consistent with Ca 2ϩ regulation in the superficial buffer barrier (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adult female Yucatan miniature swine (Charles River; Wilmington, MA) were randomly assigned to either sedentary (SED) or exercise-trained (EX) groups. EX pigs underwent 16 wk of a progressive treadmill exercise-training program used extensively by our laboratories and described previously (7,8,33,41,42). Treadmill performance tests were administered before and after completion of the 16-wk exercise-training program or sedentary confinement as described previously (7,8).…”
Section: Exercise Training Proceduresmentioning
confidence: 99%